PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN (BPKP) JAKARTA TIMUR - Asep Sulaeman; Komarudin Komarudin; Suharni Rahayu (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The purpose of this study is to identify the partial and simultaneous effects of management style and work environment on employee performance at the East Jakarta Financial and Development Supervisory Agency (BPKP). Quantitative methodology is employed. In this study, samples of 112 respondents were acquired using the random sampling technique. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are that leadership style has a significant effect on employee performance with a regression value of 0.472, a correlation value of 0.559 and a coefficient of determination of 40.7%. The work environment has a significant effect on employee performance with a regression value of 0.532, a correlation value of 0.516 and a coefficient of determination of 40.7%. Leadership style and work environment have a significant effect on employee performance with a correlation value of 0.638 and a coefficient of determination of 63.8%. This finding explains that leadership style and work environment play an important role in determining employee performance. In this context, it is important for organizations and leaders to pay attention to and improve these aspects in order to improve overall employee performance.